Erosion of Self-Efficacy as a Predictor of Burnout Among School Counselors: A Narrative Review - Ismah; Haryono; Sugiyo; Awalya (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study systematically reviews how erosion of self-efficacy predicts burnout among school counselors by synthesizing nine empirical studies published between 2015 and 2025 using PRISMA 2020 and Kitchenham’s SLR framework. Findings show that declining self-efficacy consistently predicts higher emotional exhaustion, depersonalization, and reduced personal accomplishment. Self-efficacy also mediates the relationship between job resources (role clarity, supervision, training) and counselor well-being, while loneliness and weak organizational support attenuate the protective effects of self-efficacy. Contextual vulnerabilities include crisis management and parental collaboration, where demands often exceed counselors’ capacities. Based on integrated evidence, the study proposes a context-sensitive early-detection framework for Indonesian schools that integrates organizational supports, mastery experiences, and emotional-spiritual interventions. Contributions are threefold: theoretical extension of the Job Demands Resources model, empirical validation of self-efficacy erosion as a predictor of burnout, and practical guidance for prevention. Future research should validate detection instruments and use longitudinal, mixed-method designs in Indonesian settings and implementation studies. Keywords: burnout, school counselors, self-efficacy, loneliness, systematic literature review